Hydromechanical Properties of Gas Hydrate‐Bearing Fine Sediments From In Situ Testing. Issue 11 (28th November 2018) - Taleb, F.; Garziglia, S.; Sultan, N.
Abstract: The hydromechanical properties of gas hydrate‐bearing sediment are key in assessing offshore geohazards and the resource potential of gas hydrates. For sandy materials, such properties were proved highly dependent on hydrate content ( S h ) as well as on their distribution and morphology. Owing to difficulties in testing gas hydrate‐bearing clayey sediments, the impact of hydrates on the behavior of such materials remains poorly understood. Hence, to provide insight into the characterization of clayey sediments containing hydrate, this study relies on a unique database of in situ acoustic, piezocone, and pore pressure dissipation measurements collected in a high gas flux system offshore Nigeria. Compressional wave velocity measurements were used as means of both detecting and quantifying gas hydrate in marine sediments. The analysis of piezocone data in normalized soil classification charts suggested that contrary to hydrate‐bearing sands, the behavior of gas hydrate‐bearing clays tends to be contractive. Correlations of acoustic and geotechnical data have shown that the stiffness and strength tend to increase with increasing S h . However, several sediment intervals sharing the same S h have revealed different features of mechanical behavior; suggesting that stiffness and strength of gas hydrate‐bearing clays are influenced by the distribution/morphology of gas hydrate. Pore pressure dissipation data confirmed the contractive behavior of gas hydrate‐bearing clays and showed that at low hydrate content, the hydraulic diffusivity ( C h ) decreases when S h increases. However, for S h exceeding 20%, it was shown that an increase of C h with S h could be linked to the presence of fractures in the hydrate‐sediment system. Key Points: Unlike hydrate‐bearing sands, the behavior of hydrate‐bearing clays proved contractive upon shearing according to in situ data Hydromechanical properties of hydrate‐bearing clays depend on hydrate content and superimposed influence of their distribution/morphology For gas hydrate contents higher than 20%, the hydraulic diffusivity increases with hydrate concentration